A study of n-doping in self-catalyzed GaAsSb nanowires using GaTe dopant source and ensemble nanowire near-infrared photodetector. (2nd October 2020) - Devkota, Shisir; Parakh, Mehul; Johnson, Sean; Ramaswamy, Priyanka; Lowe, Michael; Penn, Aubrey; Reynolds, Lew; Iyer, Shanthi
Abstract: This work reports a comprehensive investigation of the effect of gallium telluride (GaTe) cell temperature variation (TGaTe ) on the morphological, optical, and electrical properties of doped-GaAsSb nanowires (NWs) grown by Ga-assisted molecular beam epitaxy (MBE). These studies led to an optimum doping temperature of 550 °C for the growth of tellurium (Te)-doped GaAsSb NWs with the best optoelectronic and structural properties. Te incorporation resulted in a decrease in the aspect ratio of the NWs causing an increase in the Raman longitudinal optical/transverse optical vibrational mode intensity ratio, large photoluminescence emission with an exponential decay tail on the high energy side, promoting tunnel-assisted current conduction in ensemble NWs and significant photocurrent enhancement in the single nanowire. A Schottky barrier photodetector (PD) using Te-doped ensemble NWs with broad spectral range and a longer wavelength cutoff at ∼1.2 µ m was demonstrated. These PDs exhibited responsivity in the range of 580–620 A W −1 and detectivity of 1.2–3.8 × 10 12 Jones. The doped GaAsSb NWs have the potential for further improvement, paving the path for high-performance near-infrared (NIR) photodetection applications.